STRATEGI MENINGKATKAN EKSISTENSI USAHA INDUSTRI PAKAIAN JADI DI KOTA PEKANBARU PADA MASA PANDEMI COVID-19 - Rahayu Welda; Hendriani Susi; Fitri Kurniawaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study seeks to investigate the influence of the strategies carried out bysmall and medium-sized industries during the Covid-19 Pandemic in the form ofproduct innovation, building partners and online marketing systems asmoderating variables in developing their business existence from surveysconducted to the apparel industry in Pekanbaru City. The population in this studyare business actors in the apparel industry with a sample of 78 people calculatedusing the Slovin formula. Multiple regression using SPSS was used for dataanalysis. This result The study highlights three important points. First, ProductInnovation has a positive and significant impact on Business. Respondents'answers indicate that innovation is still lacking even though they have tried tomodify it products where the innovation has not been able to attract the attentionof consumers. Second, building partners has a positive impact andsignificantinfluence on Business Existence. Business actors, on the other hand, are stillunable to reach an agreement with their partners. The downside is that existingpartnerships are not based on legal issues. Third, the Online Marketing Systemdoes not moderate the effect of product innovation and partner building onbusiness existence. Almost all business actors cannot market their products wellonline. Business actors cannot disseminate information on social media, do notexplain product quality produced to consumers, and have problems using onlinemedia. Keywords: Business Existence, Product Innovation, Partner Development,Online MarketingSystem